2014
DOI: 10.1103/physrevlett.112.259901
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Quantum Phase Diagram of the Triangular-LatticeXXZModel in a Magnetic Field [Phys. Rev. Lett. 112, 127203 (2014)]

Abstract: We have realized that the transition between the up-up-down and 0-coplanar states near the Ising limit is actually of the first order, although the hysteresis region is very narrow. In Fig. 1(a), we present the corrected quantum phase diagram, in which the boundary of the corresponding transition for 0 < J=J z < 0.437 is replaced by a thick blue line. This minor correction does not affect the rest of the phase diagram and the main conclusions of our Letter, including the novel degeneracy-lifting mechanism that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
167
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(183 citation statements)
references
References 2 publications
12
167
4
Order By: Relevance
“…has recently received increasing attention since the latest theoretical studies [29,30] indicated the possibility for the emergence of a new magnetic phase, named the π-coplanar or Ψ phase for J > J z > 0.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…has recently received increasing attention since the latest theoretical studies [29,30] indicated the possibility for the emergence of a new magnetic phase, named the π-coplanar or Ψ phase for J > J z > 0.…”
Section: Introductionmentioning
confidence: 99%
“…1). Whereas the former two already exist in the classical counterpart of the model [31], the latter emerges due to quantum-mechanical effects [29]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction.-The S = 1/2 triangular-lattice Heisenberg antiferromagnet (TLHAF) is the paradigmatic example of a two-dimensional (2D) frustrated quantum magnet [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The combination of frustration, strong quantum fluctuations and low dimensionality is anticipated to produce strong deviations from semiclassical theories.…”
mentioning
confidence: 99%
“…• structure were compared as the "ab" and "ac" plane models, which are favored by easy-plane and easy-axis anisotropy, respectively [11,12,33]. The ab plane model corresponds to a 120…”
mentioning
confidence: 99%